2015
DOI: 10.1075/ml.10.1.03cla
|View full text |Cite
|
Sign up to set email alerts
|

Morphology constrains native and non-native word formation in different ways

Abstract: The role of morphological and syntactic information in non-native second language (L2) comprehension is controversial. Some have argued that late bilinguals rapidly integrate grammatical cues with other information sources during reading or listening in the same way as native speakers. Others claim that structural cues are underused in L2 processing. We examined different kinds of modifiers inside compounds (e.g. singulars vs. plurals, *rat eater vs. rats eater) with respect to this controversy, which are subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 46 publications
(86 reference statements)
0
10
0
Order By: Relevance
“…Lardiere (1995) argued that the morphological constraint is inoperative in the L2 as regular plurals are not consistently omitted (i.e., in more than 75% of trials) from modifiers inside compounds. Other researchers observed that like L1 speakers, L2 learners judge compounds with regular plural nonheads as less acceptable and produce them less commonly than those with irregular plural and singular nonheads, concluding that L2 learners are indeed sensitive to the compounding constraints (e.g., Clahsen, 1995; Clahsen et al, 2015; García Mayo, 2006; Murphy, 2000). How can this apparent paradox be resolved?…”
Section: Developing the Shallow Structure Hypothesismentioning
confidence: 99%
See 2 more Smart Citations
“…Lardiere (1995) argued that the morphological constraint is inoperative in the L2 as regular plurals are not consistently omitted (i.e., in more than 75% of trials) from modifiers inside compounds. Other researchers observed that like L1 speakers, L2 learners judge compounds with regular plural nonheads as less acceptable and produce them less commonly than those with irregular plural and singular nonheads, concluding that L2 learners are indeed sensitive to the compounding constraints (e.g., Clahsen, 1995; Clahsen et al, 2015; García Mayo, 2006; Murphy, 2000). How can this apparent paradox be resolved?…”
Section: Developing the Shallow Structure Hypothesismentioning
confidence: 99%
“…It soon became clear, however, that “more fine-grained linguistic distinctions are required to understand the nature of L2 morphological processing, beyond the basic procedural vs. declarative difference” (Clahsen, Felser, Neubauer, Sato, & Silva, 2010, p. 39). To provide two examples, advanced L2 learners were found to exhibit nativelike priming patterns for productive derived word forms but not for equally productive inflected forms (Kirkici & Clahsen, 2013), and lexical constraints on word-formation processes were found to affect L2 processing in the same way as L1 processing, whereas morphological constraints showed reduced effects (Clahsen, Balkhair, Schutter, & Cunnings, 2013; Clahsen, Gerth, Heyer, & Schott, 2015). These findings led us to extend the SSH to the processing of morphologically complex words (see, e.g., Clahsen et al, 2013, p. 25; Clahsen et al, 2015, p. 81; Krause, Bosch, & Clahsen, 2015, p. 618).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers have claimed that native (L1) and non-native (L2) speakers apply the same mechanisms for processing morphologically complex words, but that L2 processing may be negatively affected by difficulties with lexical access or retrieval, working memory limitations, and/or slower processing speed (e.g., Cunnings, 2017; Hopp, 2016; McDonald, 2006). Alternatively, more substantial L1/L2 differences have been posited by the Shallow-Structure Hypothesis (SSH), originally for sentence processing (Clahsen & Felser, 2006a, 2006b) and later extended to morphological processing (e.g., Clahsen, Felser, Neubauer, Sato & Silva, 2010; Clahsen, Balkhair, Schutter & Cunnings, 2013; Clahsen, Gerth, Heyer & Schott, 2015). The SSH holds that even proficient L2 speakers tend to have problems building or manipulating abstract grammatical representations in real time, and that relative to native speakers, L2 processing of morphologically complex words relies more heavily on storage of complex forms and less on morphological structure and computation.…”
Section: Introductionmentioning
confidence: 99%
“…The next constraint, SEMSING, is violated by non-heads with plural SEMANTICS and explains why irregular plurals inside compounds are less acceptable than singulars. This difference in acceptability is typically smaller than the one between regular and irregular non-heads (Clahsen, Gerth, Heyer & Schott, 2015); therefore, we attribute a smaller weight to SEMSING than to MORPHSTEM. The plurals-in-compounds effect has also been argued to result from a PHONOLOGICAL constraint against sibilant codas.…”
mentioning
confidence: 97%